Measuring and Modeling the Performance of Rigid Ceramic Filters - Chuah M, T G; Seville, J P K (ASEAN Journal of Chemical Engineering, 2002)
Rigid ceramic filters have been proven to be highly efficient gas filtration devices. However, they must be cleaned periodically for maximum efficiency. This is done by applying a pulsed reverse flow. The cleaning mechanism by which the deposited dirt is removed from the filter surface is still not fully understood. Experiments were carried out to measure pressure drop along the axis of two different candle geometry, cylindrical and tapered. For the cylindrical filter, the reverse pulse pressure was not uniformly distributed along the element. Generally, the pressure difference across the wall of the element is highest at the close end, and lowest, sometimes close to zero, at the open end. Pressure drop across the tapered filter was more uniform compared to that of the cylindrical filter. Hence, it should demonstrate better filter dirt removal. The authors have written a computer program that models the flow of the reverse pulse from the cleaning bar nozzle to the dirty side of the filter. It uses the iterative calculation mode and allows variables such as reverse pulse pressure and filter geometry to be changed. The calculations demonstrate fair agreement with the experimental results.